New Concepts in the Pathogenesis, Diagnosis and Control of Diseases Caused by the Bovine Viral Diarrhea Virus - Radostits, Otto M. (1988)
The new information on the pathogenesis and epidemiology of mucosal disease of cattle is reviewed. It is now known that clinical mucosal disease occurs only in cattle which were infected with a pestivirus in early gestation and were born with persistent viral infection and specific immunotolerance. These animals may be clinically normal at birth but may develop fatal mucosal disease, perhaps following superinfection with another pestivirus, usually between 6 and 24 months of age. They may also remain clinically normal indefinitely and breed successfully. The progeny from persistently infected females will similarly be persistently viremic, and maternal families of such animals may be established. Congenital defects may occur when infection of the fetus occurs in mid-gestation. Although fetuses may be infected in utero in late gestation, the infections do not persist, the fetuses develop antibodies, and they appear to suffer no ill-effects. Postnatal infection can result in subclinical disease (bovine viral diarrhea) with a normal immune response; the virus may also be responsible for enhanced susceptibility to other infections, diarrhea in newborn calves, and reproductive failure. Prevention of the economically important diseases caused by the virus is dependent upon the identification and elimination of persistently viremic animals, which are reservoirs of infection, and the vaccination of immunocompetent females at least three weeks before breeding. However, because of serotypic differences between strains, there is some doubt whether vaccination will reliably provide protection against the transplacental fetal infections that are important in the pathogenesis of this disease. There is no substantial evidence to warrant the vaccination of feedlot cattle.